Constituição de zona de desenvolvimento proximal na aprendizagem de conceitos geométricos em alunos de anos iniciais tendo o GeoGebra como instrumento mediador - Jacques, Siméia Tussi (2015)
This paper views technologies as human constructs, becoming as such in the objectification process, having a specific function when shared within the social practice. Among the technologies, it is possible to highlight the media inventions for having multiple utilities alongside the accumulated human intelligence in producing and reproducing its material life, modifying the human relationships and nature. The school, considered as a privileged place where knowledge is shared, faces the paradigm to follow the path done by the intellectual human development, besides ensuring the re-flexibility on the actions as we establish in the world. It is pictured, in school, the singular role of teacher and students, in mediated relationships aiming at achieving the human culture. It is important to focus attention on that issue, in order to reflect on the purpose of teaching geometrical concepts, using the mediating software called GeoGebra. Nevertheless, it is not any type of teaching that accepts the majority of formation concepts, as well as by the fact that it is not any mediation that qualifies for such process, under the zone of proximal development (ZPD) perspective, based on the cultural-historical theory. It was performed a qualitative field research focused on the cultural historical perspective among 5th graders of Elementary School attending a private school in Santa Maria/RS. As for the methodological procedures, it was selected the participant-observation, semi-structured interview followed by an opened questionnaire and field journal, besides the elaboration of activities created in the GeoGebra software and digital records. The analysis of content was used for data analysis, therefore being characterized by the different methodological resources. As for the results, it is possible to conclude that the digital tools are an indirect means for human action around him, alongside his presence in the educational context as changing the teaching perspectives. On the other hand, in order to transformations of spontaneous knowledge into scientific knowledge occur, the child needs, undoubtedly, the teacher to act as the organizer of activities to foster learning, promoting collaborative actions to reach their goals.